Nicotiana benthamiana RanBP1-1 Is Involved in the Induction of Disease Resistance via Regulation of Nuclear-Cytoplasmic Transport of Small GTPase Ran - Mizuno, Yuri; Ohtsu, Mina; Shibata, Yusuke; Tanaka, Aiko; Camagna, Maurizio; Ojika, Makoto; Mori, Hitoshi; Sato, Ikuo; Chiba, Sotaro; Kawakita, Kazuhito; Takemoto, Daigo (Frontiers in Plant Science, 2019)
Plant cells enhance the tolerances to abiotic and biotic stresses via recognition of the stress, activation and nuclear import of signaling factors, up-regulation of defense genes, nuclear export of mRNA and translation of defense proteins. Nuclear pore-mediated transports should play critical roles in these processes, however, the regulatory mechanisms of nuclear-cytoplasmic transport during stress responses are largely unknown. In this study, a regulator of nuclear export of RNA and proteins, NbRanBP1-1 (Ran-binding protein1-1), was identified as an essential gene for the resistance of Nicotiana benthamiana to potato blight pathogen Phytophthora infestans. NbRanBP1-1-silenced plants showed delayed accumulation of capsidiol, a sesquiterpenoid phytoalexin, in response to elicitor treatment, and reduced resistance to P. infestans. Abnormal accumulation of mRNA was observed in NbRanBP1-1-silenced plants, indicating that NbRanBP1-1 is involved in the nuclear export of mRNA. In NbRanBP1-1-silenced plants, elicitor-induced expression of defense genes, NbEAS and NbWIPK, was not affected in the early stage of defense induction, but the accumulation of NbWIPK protein was reduced. Nuclear export of the small G-protein NbRan1a was activated during the induction of plant defense, whereas this process was compromised in NbRanBP1-1-silenced plants. Silencing of genes encoding the nuclear pore proteins, Nup75 and Nup160, also caused abnormal nuclear accumulation of mRNA, defects in the nuclear export of NbRan1a, and reduced production of capsidiol, resulting in decreased resistance to P. infestans. These results suggest that nuclear export of NbRan is a key event for defense induction in N. benthamiana, and both RanBP1-1 and nucleoporins play important roles in the process.